Planning And Solution of Urban Infrastructure Problems Through the Integration of Collaborative GIS And Public Participation GIS - Mohamad Syahrul Gunawan; Yana Syafriyana Hijri; Salahudin Salahudin; Iradhad Taqwa Sihidi (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study aims to research related to planning and solving urban infrastructure problems with the Literature Review method, namely reading and reviewing main ideas on the same topic to add and also strengthen the arguments and views or opinions of the author on the topic to be raised in this study. In addition, by using a review paper, the authors can also see the shortcomings of previous studies so that they can make improvements and a more regular and systematic formulation. This research reveals that in the planning process infrastructure development must have the impact and consequences of development planning so that problems do not occur in the development process. In the development process, another thing is to look at the environmental impact of infrastructure that will later be generated from development projects that will be initiated primarily in an urban area that has modern characteristics by involving the community in carrying out infrastructure development. In conducting this research, infrastructure is also a very important part of infrastructure. for an experience because it has a very large impact on growth and the economy in a country, especially Indonesia, therefore the purpose of this study is to examine and see the results of the journal a know the existing data